Influence of the Frequency-chirp on Pulse in Passively Mode-locking Optical Fiber Ring Laser - Kien, Bui Xuan; Hung, Tran Hai; Chien, Trinh Dinh (Communications in Physics, 2013)
We consider a model of a passively mode-locking fiber ring laser bult using a saturable absorber and a chirped fiber Bragg grating to balance dispersion and nonlinearity. The evolution of the slowly envelope of the optical field in a loop fiber subject to dispersion , Kerr nonlinearity, frequency- chirp and nonlinear absorption is given by the generalized complex Ginzburg-Landau equation. The influence of the frequency-chirp on the pulse is simulated and discussed, and the stationary conditions concerning the chirp parameter are found out for our laser.